Adhesion film forming material, method for forming adhesion film using same, and method for forming pattern using adhesion film forming material

The adhesive film forming material with specific components addresses the issue of pattern collapse in multilayer resist methods by enhancing adhesion and stability, enabling precise pattern formation in semiconductor manufacturing.

JP7611785B2Active Publication Date: 2025-01-10SHIN ETSU CHEMICAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021112381
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-06
Publication Date
2025-01-10
Estimated Expiration
2041-07-06

AI Technical Summary

Technical Problem

The challenge of pattern collapse in fine patterning processes during semiconductor manufacturing due to low etching resistance and adhesion issues in photoresist compositions, particularly with the use of multilayer resist methods, is not adequately addressed by existing materials, leading to incomplete pattern transfer and substrate damage.

Method used

An adhesive film forming material comprising a resin with specific structural units, a crosslinking agent, a photoacid generator, and an organic solvent is used to form an adhesive film between a silicon-containing intermediate film and a resist upper layer film, enhancing adhesion and suppressing pattern collapse.

Benefits of technology

The adhesive film material improves adhesion to the resist upper layer film, effectively prevents pattern collapse, and allows for precise pattern formation in multilayer resist processes, ensuring high precision and stability in semiconductor device manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007611785000049
    Figure 0007611785000049
  • Figure 0007611785000050
    Figure 0007611785000050
  • Figure 0007611785000001
    Figure 0007611785000001
Patent Text Reader

Abstract

To provide an adhesion film-forming material having high adhesion with a resist upper layer film, having collapse suppression effect of a fine pattern, and giving an adhesion film capable of forming a good pattern figuration in a fine patterning process by a multilayer resist method in a semiconductor device production process, a method of forming a pattern using the material, and a method of forming the adhesion film.SOLUTION: An adhesion film-forming material of an adhesion film formed between a silicon-containing intermediate film and a resist upper layer film includes: a resin having a specific structural unit having a phenolic hydroxyl group; a crosslinking agent containing one or more compound(s) represented by formula (2); an optical acid generator; and an organic solvent.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesion film-forming material, a method for forming an adhesion film using the adhesion film-forming material, and a method for forming a pattern using the adhesion film-forming material. [Background technology]

[0002] As LSIs become more highly integrated and faster, pattern dimensions are becoming finer. Lithography technology has achieved the formation of fine patterns by shortening the wavelength of light sources and appropriately selecting resist compositions to match them, in line with this miniaturization. The core of this technology is a positive photoresist composition used in a single layer. This single-layer positive photoresist composition has a skeleton in the resist resin that is resistant to dry etching using chlorine- or fluorine-based gas plasma, and has a resist mechanism that dissolves the exposed parts, so that the exposed parts are dissolved to form a pattern, and the remaining resist pattern is used as an etching mask to dry etch the substrate to which the photoresist composition has been applied.

[0003] However, if the thickness of the photoresist film used is kept the same and the pattern width is made smaller, the resolution of the photoresist film decreases, and if the photoresist film is developed into a pattern using a developer, the aspect ratio becomes too large, resulting in pattern collapse. For this reason, the thickness of the photoresist film has been made thinner as the pattern becomes finer.

[0004] On the other hand, in the processing of the substrate to be processed, a method is used in which the substrate to be processed is processed by dry etching using a photoresist film on which a pattern is usually formed as an etching mask, but in reality, there is no dry etching method that can obtain complete etching selectivity between the photoresist film and the substrate to be processed, so that the photoresist film is also damaged during the processing of the substrate to be processed, and the photoresist film collapses during the processing of the substrate to be processed, making it impossible to accurately transfer the resist pattern to the substrate to be processed. Therefore, with the miniaturization of patterns, photoresist compositions are required to have high dry etching resistance. In addition, as the exposure wavelength becomes shorter, the resin used in the photoresist composition is required to have low light absorption at the exposure wavelength, so that in response to the change to i-line, KrF, and ArF, novolac resins, polyhydroxystyrene, and resins with aliphatic polycyclic skeletons have been used. However, in reality, the etching speed under the above dry etching conditions has become fast, and recent photoresist compositions with high resolution tend to have weak etching resistance.

[0005] For this reason, it has become necessary to dry etch the substrate to be processed using a thinner photoresist film with a weaker etching resistance, and securing the materials and processes for this processing step has become an urgent need.

[0006] One method for solving such problems is the multi-layer resist method, in which an intermediate film having a different etching selectivity from the photoresist film (i.e., resist top layer film) is interposed between the resist top layer film and the substrate to be processed, and after a pattern is obtained in the resist top layer film, the pattern is transferred to the intermediate film by dry etching using the resist top layer film pattern as a dry etching mask, and the pattern is further transferred to the substrate to be processed by dry etching using the intermediate film as a dry etching mask.

[0007] One of the multilayer resist methods is a three-layer resist method that can be performed using a general resist composition used in a single-layer resist method. In this three-layer resist method, for example, an organic film made of novolac or the like is formed on a substrate to be processed as a resist underlayer film, a silicon-containing film is formed thereon as a silicon-containing resist intermediate film, and a normal organic photoresist film is formed thereon as a resist upper layer film. For dry etching with fluorine-based gas plasma, the organic resist upper layer film has a good etching selectivity to the silicon-containing resist intermediate film, so the resist upper layer film pattern is transferred to the silicon-containing resist intermediate film by using dry etching with fluorine-based gas plasma. Furthermore, for etching with oxygen gas or hydrogen gas, the silicon-containing resist intermediate film can have a good etching selectivity to the resist underlayer film, so the silicon-containing intermediate film pattern is transferred to the resist underlayer film by etching with oxygen gas or hydrogen gas. According to this method, even if a photoresist composition is used that is difficult to form a pattern with a sufficient film thickness for directly processing a substrate to be processed, or a photoresist composition that does not have sufficient dry etching resistance for processing a substrate, if a pattern can be transferred to a silicon-containing film (silicon-containing resist intermediate film), a pattern of an organic film (resist underlayer film) made of novolak or the like that has sufficient dry etching resistance for processing can be obtained.

[0008] On the other hand, in recent years, ArF immersion lithography has Rough With the advent of lithography, EUV lithography, etc., it is becoming possible to form finer patterns, but on the other hand, ultra-fine patterns are extremely prone to collapse due to their small contact area, and suppressing pattern collapse is a major issue. Recently, it is said that the interaction at the interface between the resist top layer film and the resist bottom layer film in fine patterns affects pattern collapse, and there is a need to improve the performance of the resist bottom layer film.

[0009] In order to suppress pattern collapse, materials have been reported that improve adhesion to the resist upper layer film by using a resist underlayer film containing a polar functional group such as a lactone structure or a urea structure (Patent Documents 1 and 2). However, in the current situation where finer pattern formation is required, it cannot be said that these materials have sufficient pattern collapse suppression performance. Furthermore, a resist underlayer film that combines a resin containing a phenolic hydroxyl group and a compound having a vinyl ether group has been reported, but its thermosetting property is not sufficient (Patent Document 3). For the above reasons, a material with higher pattern collapse suppression performance and adhesion is required. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] International Publication No. 2003 / 017002 [Patent Document 2] International Publication No. 2018 / 143359 [Patent Document 3] Patent No. 5708938 Summary of the Invention [Problem to be solved by the invention]

[0011] The present invention has been made in consideration of the above circumstances, and has an object to provide an adhesion film forming material that provides an adhesion film that has high adhesion to an overlying resist film, has an effect of preventing collapse of a fine pattern, and is capable of forming a good pattern shape in a fine patterning process using a multilayer resist method in a semiconductor device manufacturing process, a pattern formation method using the material, and a method for forming the adhesion film. [Means for solving the problem]

[0012] In order to solve the above problems, the present invention provides an adhesion film-forming material for an adhesion film formed between a silicon-containing intermediate film and a resist upper layer film, the adhesion film-forming material comprising (A) a resin having a structural unit represented by the following general formula (1), (B) a crosslinking agent containing one or more compounds represented by the following general formula (2), (C) a photoacid generator, and (D) an organic solvent: [ka] (In the formula, R 01 is a hydrogen atom or a methyl group, R 02 is an alkyl group having 1 to 3 carbon atoms, m is an integer of 1 or 2, n is an integer of 0 to 4, and m+n is an integer of 1 or more and 5 or less. X is a single bond or an alkylene group having 1 to 10 carbon atoms which may contain an oxygen atom. [ka] (In the formula, Q is a single bond or a q-valent hydrocarbon group having 1 to 20 carbon atoms. R 03 is a hydrogen atom or a methyl group. q is an integer of 1 to 5.

[0013] Such an adhesive film-forming material can form an adhesive film that has high adhesion to the resist upper layer film, has the effect of preventing the fine pattern from collapsing, and gives a good pattern shape.

[0014] In the present invention, the silicon-containing intermediate film is preferably a silicon-containing resist intermediate film or an inorganic hard mask intermediate film.

[0015] In the present invention, such an interlayer film can be suitably used as the silicon-containing interlayer film.

[0016] In the present invention, the (C) photoacid generator preferably contains one or more compounds represented by the following general formula (3). [ka] (In the formula, R04 , R 05 and R 06 each independently represents a linear alkyl or alkenyl group having 1 to 10 carbon atoms, which may be substituted with a heteroatom or may have a heteroatom interposed therebetween, or a branched or cyclic alkyl or alkenyl group having 3 to 10 carbon atoms, which may be substituted with a heteroatom or may have a heteroatom interposed therebetween, or an aryl or aralkyl group having 6 to 18 carbon atoms, which may be substituted with a heteroatom or may have a heteroatom interposed therebetween. 04 , R 05 and R 06 Any two of Y may be bonded to each other to form a ring together with the sulfur atom in the formula. - represents either the following general formula (4) or (5). [ka] (In the formula, R 07 and R 08 each independently represents a monovalent hydrocarbon group containing an aliphatic ring structure having 3 to 40 carbon atoms, which may be substituted with a heteroatom and which may be interrupted by a heteroatom.

[0017] Such an adhesive film-forming material has the effect of preventing collapse of a fine pattern, and also allows appropriate adjustment of the pattern shape, exposure sensitivity, etc. of the resist upper layer film.

[0018] In this case, the general formula (4) is preferably represented by the following general formula (4'). [ka] (In the formula, R 09 R represents a hydrogen atom or a trifluoromethyl group. 10 represents a monovalent hydrocarbon group containing an aliphatic ring structure having 3 to 30 carbon atoms, which may be substituted with a heteroatom or which may be interrupted by a heteroatom.

[0019] Such an adhesive film-forming material has sufficient acidity, and allows for appropriate adjustment of acid diffusion, and may also be effective in reducing residues derived from the upper layer film of the resist.

[0020] In the present invention, it is preferable that X in the general formula (1) is -C(=O)O-.

[0021] Such an adhesive film-forming material can form an adhesive film that has higher adhesion to the resist upper layer film and has the effect of preventing the collapse of a fine pattern.

[0022] In the present invention, the weight average molecular weight of the (A) resin is preferably 1,000 to 20,000.

[0023] An adhesive film-forming material containing a resin having such a weight-average molecular weight range has excellent film-forming properties, suppresses the generation of sublimates during heat curing, and suppresses contamination of the device caused by the sublimates. In addition, the occurrence of coating defects can be suppressed, resulting in an even more excellent adhesive film-forming material.

[0024] In the present invention, the content of the (B) crosslinking agent is preferably 10% by mass to 50% by mass relative to the content of the (A) resin.

[0025] Such an adhesive film-forming material has increased crosslinking reactivity, which improves the solvent resistance of the adhesive film, and also makes it possible to form an adhesive film that maintains high adhesion to the resist upper layer film.

[0026] In the present invention, the content of the (C) photoacid generator is preferably 1% by mass to 20% by mass relative to the content of the (A) resin.

[0027] Such an adhesive film-forming material allows appropriate adjustment of the pattern shape, exposure sensitivity, etc. of the resist upper layer film, and is suitable for photolithography of the resist upper layer film.

[0028] In the present invention, it is preferable to further contain one or more of a surfactant, a plasticizer, and a dye.

[0029] The presence or absence / selection of these various additives makes it possible to fine-tune the performance, such as film-forming properties, embedding properties, and optical properties, in accordance with customer requirements, which is preferable from a practical standpoint.

[0030] In the present invention, it is preferable that the composition does not contain a thermal acid generator.

[0031] Such an adhesion film-forming material can prevent the adhesion film surface from becoming acidic after baking, and the acid generated from diffusing into the resist upper layer film can prevent the pattern shape from becoming undercut, which induces pattern collapse, or conversely, prevents the pattern from becoming bottom-heavy.

[0032] The present invention also provides a method for forming a pattern on a workpiece substrate, comprising the steps of: (I-1) forming a resist underlayer film on a substrate to be processed; (I-2) forming a silicon-containing resist intermediate film on the resist underlayer film; (I-3) a step of applying the above-described adhesion film-forming material onto the silicon-containing resist intermediate film, followed by heat treatment to form an adhesion film; (I-4) forming a resist top layer film on the adhesion film using a photoresist material; (I-5) a step of forming a pattern on the resist upper layer film by pattern-exposing the resist upper layer film and then developing the resist upper layer film with a developer; (I-6) a step of transferring the pattern to the adhesion film by dry etching using the resist upper layer film on which the pattern has been formed as a mask; (I-7) a step of transferring the pattern to the silicon-containing resist intermediate film by dry etching using the adhesion film on which the pattern is formed as a mask; and (I-8) a step of transferring a pattern to the resist underlayer film by dry etching using the silicon-containing resist intermediate film to which the pattern has been transferred as a mask; The present invention provides a pattern forming method comprising the steps of:

[0033] The present invention also provides a method for forming a pattern on a workpiece substrate, comprising the steps of: (II-1) forming a resist underlayer film on a substrate to be processed; (II-2) forming an inorganic hard mask intermediate film selected from a silicon oxide film, a silicon nitride film, and a silicon oxynitride film on the resist underlayer film; (II-3) A step of forming an adhesion film by applying the above-described adhesion film forming material onto the inorganic hard mask intermediate film and then performing a heat treatment; (II-4) forming a resist top layer film on the adhesion film using a photoresist material; (II-5) a step of forming a pattern on the resist upper layer film by pattern-exposing the resist upper layer film and then developing the resist upper layer film with a developer; (II-6) a step of transferring the pattern to the adhesion film by dry etching using the resist upper layer film on which the pattern is formed as a mask; (II-7) a step of transferring the pattern to the inorganic hard mask intermediate film by dry etching using the adhesive film on which the pattern is formed as a mask; and (II-8) a step of transferring a pattern to the resist underlayer film by dry etching using the inorganic hard mask intermediate film to which the pattern has been transferred as a mask; The present invention provides a pattern forming method comprising the steps of:

[0034] In this way, the adhesion film-forming material of the present invention can be suitably used in various pattern formation methods, such as a four-layer resist process in which the adhesion film is formed on a silicon-containing intermediate film (silicon-containing resist intermediate film, inorganic hard mask intermediate film). In these pattern formation methods, the formation of the adhesion film can effectively reduce pattern collapse, and is suitable for photolithography of a resist upper layer film.

[0035] In this case, it is preferable that the inorganic hard mask intermediate film is formed by a CVD method or an ALD method.

[0036] In the present invention, the method for forming a circuit pattern on the resist upper layer film is preferably photolithography with a wavelength of 10 nm or more and 300 nm or less, direct writing with an electron beam, nanoimprinting, or a combination of these.

[0037] In the present invention, it is preferable to use an alkali development or an organic solvent development as a development method.

[0038] In the present invention, by using the above-mentioned pattern formation method, the pattern formation can be performed satisfactorily and efficiently.

[0039] In addition, in the present invention, it is preferable to use, as the substrate to be processed, a semiconductor device substrate, or a semiconductor device substrate having any one of a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, and a metal oxide nitride film formed thereon.

[0040] In this case, the metal is preferably silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or an alloy thereof.

[0041] According to the pattern forming method of the present invention, a pattern can be formed by processing the above-mentioned substrate to be processed in the above-mentioned manner.

[0042] The present invention also provides a method for forming an adhesion film that functions as an adhesion layer used in the manufacturing process of a semiconductor device, which comprises spin-coating the above-mentioned adhesion film-forming material on a substrate to be processed, and heat-treating the substrate coated with the adhesion film-forming material at a temperature of 100°C or higher and 300°C or lower for 10 to 600 seconds to form a hardened film.

[0043] The present invention also provides a method for forming an adhesion film that functions as an adhesion layer used in the manufacturing process of a semiconductor device, which comprises spin-coating the above-mentioned adhesion film-forming material on a substrate to be processed, and heat-treating the substrate coated with the adhesion film-forming material in an atmosphere having an oxygen concentration of 0.1% or more and 21% or less to form a hardened film.

[0044] By using such a method, the crosslinking reaction during the formation of the adhesive film can be promoted, and mixing with the resist upper layer film can be more effectively suppressed. In addition, by appropriately adjusting the heat treatment temperature, time, and oxygen concentration within the above ranges, it is possible to obtain an effect of suppressing the collapse of the pattern of the adhesive film suitable for the application, and to obtain the pattern shape adjustment property of the resist upper layer film.

[0045] The present invention also provides a method for forming an adhesion film that functions as an adhesion layer used in the manufacturing process of a semiconductor device, which comprises spin-coating the above-mentioned adhesion film-forming material on a substrate to be processed, and heat-treating the substrate coated with the adhesion film-forming material in an atmosphere with an oxygen concentration of less than 0.1%, thereby forming a hardened film.

[0046] This method is useful because it promotes the crosslinking reaction during the formation of the adhesion film and more highly suppresses intermixing with the overlying film without causing deterioration of the substrate to be processed, even if the substrate contains a material that is unstable when heated in an oxygen atmosphere. Effect of the Invention

[0047] As described above, the present invention can provide an adhesive film-forming material that has high adhesion to the resist top layer film and has a fine pattern collapse suppressing effect. In addition, this adhesive film-forming material has high adhesion and has a fine pattern collapse suppressing effect, and can appropriately adjust the pattern shape and exposure sensitivity of the resist top layer film, so it is extremely useful in a multi-layer resist process, such as a four-layer resist process in which the adhesive film is formed on a silicon-containing intermediate film. In addition, the adhesive film forming method of the present invention can form an adhesive film that is sufficiently cured on the substrate to be processed and has high adhesion to the resist top layer film. In addition, the pattern forming method of the present invention can form a fine pattern on the substrate to be processed with high precision in the multi-layer resist process. [Brief description of the drawings]

[0048] [Figure 1] FIG. 2 is an explanatory diagram of an example of a pattern forming method using a four-layer resist process of the present invention. [Diagram 2] FIG. 2 is an explanatory diagram showing a method for measuring adhesion in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0049] As described above, in the fine patterning process using the multilayer resist method in the semiconductor device manufacturing process, there has been a demand for an adhesion film forming material that has high adhesion to an overlying resist film and has an effect of preventing the collapse of a fine pattern, a pattern formation method using said material, and a method for forming an adhesion film.

[0050] As a result of intensive research into the above-mentioned problems, the present inventors have been searching for an adhesion film-forming material that has high adhesion to a resist upper layer film by forming an adhesion film in multilayer lithography and has an effect of suppressing collapse of a fine pattern, and a pattern formation method using the material. As a result, they have found that an adhesion film-forming material mainly composed of a compound having a specific structure, a pattern formation method using the material, and a method for forming an adhesion film are very effective, and have completed the present invention.

[0051] That is, the present invention relates to an adhesion film-forming material for an adhesion film formed between a silicon-containing intermediate film and a resist upper layer film, the adhesion film-forming material comprising (A) a resin having a structural unit represented by the following general formula (1), (B) a crosslinking agent containing one or more compounds represented by the following general formula (2), (C) a photoacid generator, and (D) an organic solvent. [ka] (In the formula, R 01 is a hydrogen atom or a methyl group, R 02 is an alkyl group having 1 to 3 carbon atoms, m is an integer of 1 or 2, n is an integer of 0 to 4, and m+n is an integer of 1 or more and 5 or less. X is a single bond or an alkylene group having 1 to 10 carbon atoms which may contain an oxygen atom. [ka] (In the formula, Q is a single bond or a q-valent hydrocarbon group having 1 to 20 carbon atoms. R 03 is a hydrogen atom or a methyl group. q is an integer of 1 to 5.

[0052] The present invention will be described in detail below, but the present invention is not limited thereto.

[0053] [Adhesive film forming materials] The present invention provides an adhesion film-forming material that provides an adhesion film formed between a silicon-containing intermediate film and a resist upper layer film, the adhesion film-forming material comprising (A) a resin having a structural unit represented by the following general formula (1), (B) a crosslinking agent containing one or more compounds represented by the following general formula (2), (C) a photoacid generator, and (D) an organic solvent. In the adhesion film-forming material of the present invention, the (A) resin may be used alone or in combination of two or more. Furthermore, the adhesion film-forming material may contain components other than the above components (A) to (D). Each component will be described below.

[0054] [(A) Resin] The resin (A) contained in the adhesion film forming material of the present invention is represented by the following general formula (1). [ka] (In the formula, R 01 is a hydrogen atom or a methyl group, R 02 is an alkyl group having 1 to 3 carbon atoms, m is an integer of 1 or 2, n is an integer of 0 to 4, and m+n is an integer of 1 or more and 5 or less. X is a single bond or an alkylene group having 1 to 10 carbon atoms which may contain an oxygen atom.

[0055] R in the general formula (1) 01 is a hydrogen atom or a methyl group, R 02 is an alkyl group having 1 to 3 carbon atoms, m is an integer of 1 or 2, n is an integer of 0 to 4, and m+n is an integer of 1 or more and 5 or less, preferably m is an integer of 1 or more and n is an integer of 0 or 1, and m+n is an integer of 1 or more and 3 or less, and more preferably m is 1, n is 0, and m+n is 1.

[0056] X in the general formula (1) is a single bond or an alkylene group having 1 to 10 carbon atoms which may contain an oxygen atom. The oxygen atom in X can form a carbonyl group, a hydroxyl group, or an ether bond. For example, ether The bond is an alkylene group containing one carbon atom. As X , ingredients Specific examples include, but are not limited to, the following: [ka] (In the formula, the dashed lines represent bonds.)

[0057] R in the general formula (1) 02 Examples of the alkyl group include a methyl group, an ethyl group, a propyl group, and an isopropyl group. From the viewpoint of adhesion to the resist upper layer film, a methyl group is preferable.

[0058] Specific examples of the resin represented by the general formula (1) include, but are not limited to, the following: 01 is the same as above. [ka]

[0059] [ka]

[0060] Adhesion film-forming materials containing these resins can form adhesion film-forming materials that have high adhesion to the resist overcoat film and have the effect of preventing the collapse of fine patterns, and can be easily manufactured.

[0061] By using an adhesion film-forming material containing such a resin in the formation of a multilayer resist film that is applied to fine processing in the manufacturing process of a semiconductor device or the like, it is possible to provide an adhesion film-forming material for forming an adhesion film that has high adhesion to an overlying resist film and has the effect of preventing collapse of a fine pattern, a method for forming an adhesion film, and a method for forming a pattern.

[0062] The resin can be synthesized by polymerizing each monomer protected by a protecting group as necessary by a known method, and then carrying out a deprotection reaction as necessary. The polymerization reaction is not particularly limited, but is preferably radical polymerization or anionic polymerization. For these methods, JP-A-2004-115630 can be referred to.

[0063] The resin preferably has a weight average molecular weight (Mw) of 1,000 to 20,000, more preferably 5,000 to 15,000. If Mw is 1,000 or more, the resin has excellent film-forming properties, and can suppress the generation of sublimates during heat curing, thereby suppressing contamination of the device due to the sublimates. On the other hand, if Mw is 20,000 or less, the resin can suppress the occurrence of poor coating properties and coating defects due to insufficient solubility in a solvent. The resin also preferably has a molecular weight distribution (Mw / Mn) of 1.0 to 2.8, more preferably 1.0 to 2.5. In the present invention, Mw and molecular weight distribution are values ​​measured in terms of polystyrene by gel permeation chromatography (GPC) using tetrahydrofuran (THF) as a solvent.

[0064] [(B) Crosslinking agent] The adhesion film-forming material of the present invention contains a crosslinking agent represented by the following general formula (2) as component (B). This enhances curability and suppresses intermixing with the resist upper layer film. In addition to this effect, the film thickness uniformity may also be improved. Furthermore, the crosslinking agent represented by the following general formula (2) has a faster crosslinking rate than other crosslinking agents and can achieve sufficient curability even without a thermal acid generator. For this reason, the adhesion film-forming material of the present invention does not require a thermal acid generator and preferably does not contain one. [ka] (In the formula, Q is a single bond or a q-valent hydrocarbon group having 1 to 20 carbon atoms. R 03 is a hydrogen atom or a methyl group. q is an integer of 1 to 5.

[0065] In the general formula (2), Q is a single bond or a q-valent hydrocarbon group having 1 to 20 carbon atoms. q is an integer of 1 to 5, and more preferably 2 or 3. When Q is a q-valent hydrocarbon group having 1 to 20 carbon atoms, Q is a q-valent hydrocarbon group obtained by removing q hydrogen atoms from a hydrocarbon having 1 to 20 carbon atoms. In this case, more specific examples of the hydrocarbon having 1 to 20 carbon atoms include methane, ethane, propane, butane, isobutane, pentane, cyclopentane, hexane, cyclohexane, methylpentane, methylcyclohexane, dimethylcyclohexane, trimethylcyclohexane, benzene, toluene, xylene, ethylbenzene, ethylisopropylbenzene, diisopropylbenzene, methylnaphthalene, ethylnaphthalene, and eicosane.

[0066] R in the general formula (2) 03 is a hydrogen atom or a methyl group, and is preferably a methyl group.

[0067] Specific examples of the compound represented by the general formula (2) include, but are not limited to, the following compounds: 03 is the same as above. [ka]

[0068] [ka]

[0069] The (B) crosslinking agent can be used alone or in combination of two or more. The amount of the (B) crosslinking agent added is preferably 10% by mass to 50% by mass, more preferably 15% by mass to 30% by mass, based on the content (100% by mass) of the (A) resin. If the amount added is 10% by mass or more, sufficient curability is obtained and intermixing with the resist upper layer film can be suppressed. On the other hand, if the amount added is 50% by mass or less, the ratio of the (A) resin in the composition is low, and there is no risk of deterioration in adhesion.

[0070] [(C) Photoacid generator] The adhesive film-forming material of the present invention further contains a photoacid generator as component (C), which is preferably represented by the following general formula (3). [ka] (In the formula, R 04 , R 05 and R 06 each independently represents a linear alkyl or alkenyl group having 1 to 10 carbon atoms, which may be substituted with a heteroatom or may have a heteroatom interposed therebetween, or a branched or cyclic alkyl or alkenyl group having 3 to 10 carbon atoms, which may be substituted with a heteroatom or may have a heteroatom interposed therebetween, or an aryl or aralkyl group having 6 to 18 carbon atoms, which may be substituted with a heteroatom or may have a heteroatom interposed therebetween. 04 , R 05 and R 06 Any two of Y may be bonded to each other to form a ring together with the sulfur atom in the formula. - represents either the following general formula (4) or (5). [ka] (In the formula, R 07 and R 08 each independently represents a monovalent hydrocarbon group containing an aliphatic ring structure having 3 to 40 carbon atoms, which may be substituted with a heteroatom and which may be interrupted by a heteroatom.

[0071] In this case, it is more preferable that the general formula (4) is represented by the following general formula (4'). [ka] (In the formula, R 09 R represents a hydrogen atom or a trifluoromethyl group. 10 represents a monovalent hydrocarbon group containing an aliphatic ring structure having 3 to 30 carbon atoms, which may be substituted with a heteroatom or which may be interrupted by a heteroatom.

[0072] R in the general formula (3) 04 , R 05 and R06 Each of the groups independently represents a linear or branched or cyclic alkyl or alkenyl group having 1 to 10 carbon atoms, which may be substituted with a heteroatom or may have a heteroatom interposed therebetween, or an aryl or aralkyl group having 6 to 18 carbon atoms, which may be substituted with a heteroatom or may have a heteroatom interposed therebetween. Specific examples include alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, cyclopropyl, cyclopentyl, cyclohexyl, cyclopropylmethyl, 4-methylcyclohexyl, cyclohexylmethyl, norbornyl, and adamantyl groups; alkenyl groups such as vinyl, allyl, propenyl, butenyl, hexenyl, and cyclohexenyl groups; aryl groups such as phenyl, naphthyl, and thienyl groups; and aralkyl groups such as benzyl, 1-phenylethyl, and 2-phenylethyl groups, with aryl groups being preferred. In addition, some of the hydrogen atoms in these groups may be replaced with heteroatoms such as oxygen atoms, sulfur atoms, nitrogen atoms, and halogen atoms, or heteroatoms such as oxygen atoms, sulfur atoms, and nitrogen atoms may be present, resulting in the formation or presence of a hydroxyl group, a cyano group, a carbonyl group, an ether bond, an ester bond, a sulfonate ester bond, a carbonate bond, a lactone ring, a sultone ring, a carboxylic acid anhydride, a haloalkyl group, and the like. 04 , R 05 and R 06 Any two of these may be bonded to each other to form a ring together with the sulfur atom in the formula.

[0073] In addition, Y in the general formula (3) - is either of the above general formula (4) or (5), and specific examples include, but are not limited to, the following: 07 and R 08 each independently represents a monovalent hydrocarbon group containing an aliphatic ring structure having 3 to 40 carbon atoms which may be substituted with a heteroatom and which may be interrupted by a heteroatom, and is preferably a 1-norbornyl group, a 1-adamantyl group, a 2-adamantyl group, or a 4-oxo-1-adamantyl group. [ka]

[0074] [ka]

[0075] [ka]

[0076] [ka]

[0077] [ka]

[0078] [ka]

[0079] [ka]

[0080] [ka]

[0081] In general formula (4'), R 09 R represents a hydrogen atom or a trifluoromethyl group, and is preferably a trifluoromethyl group. 10 represents a monovalent hydrocarbon group containing an aliphatic ring structure having 3 to 30 carbon atoms which may be substituted with or interrupted by a heteroatom, and is preferably a 1-norbornyl group, a 1-adamantyl group, a 2-adamantyl group, or a 4-oxo-1-adamantyl group.

[0082] The (C) photoacid generator can be used alone or in combination of two or more to appropriately adjust the pattern shape, exposure sensitivity, etc. of the resist upper layer film. The amount of the (C) photoacid generator added is preferably 1% by mass to 20% by mass, more preferably 5% by mass to 15% by mass, based on the content (100% by mass) of the (A) resin. If the amount of the (C) photoacid generator added is within the above range, the resolution is good and there is no risk of problems with foreign matter occurring after resist development or during peeling.

[0083] [(D) Organic solvent] The organic solvent (D) contained in the adhesive film forming material used in the adhesive film forming method of the present invention is not particularly limited as long as it dissolves the resin (A), the crosslinking agent (B), the photoacid generator (C), and other additives, if any. Specifically, solvents having a boiling point of less than 180°C, such as those described in paragraphs (0091) to (0092) of JP-A-2007-199653, can be used. Among them, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, 2-heptanone, cyclopentanone, cyclohexanone, and mixtures of two or more of these are preferably used.

[0084] Such a composition can be applied by spin coating, and since it contains the adhesion film-forming material of the present invention as described above, it becomes a composition for forming an adhesion film that has high adhesion to the resist overlying film and has the effect of preventing the collapse of a fine pattern.

[0085] [Other additives] The adhesive film-forming material of the present invention may further contain one or more of a surfactant, a plasticizer and a dye in addition to the above-mentioned components (A) to (D). Each component will be described below.

[0086] (Surfactant) A surfactant can be added to the adhesive film-forming material of the present invention in order to improve the coating property in spin coating. As the surfactant, for example, those described in (0142) to (0147) of JP-A-2009-269953 can be used.

[0087] (Plasticizer) A plasticizer can be added to the adhesive film-forming material of the present invention. The plasticizer is not particularly limited, and various known plasticizers can be widely used. Examples include low molecular weight compounds such as phthalates, adipic esters, phosphates, trimellitates, and citrates, polyethers, polyesters, and polyacetal polymers described in JP-A-2013-253227.

[0088] (dye) In addition, a dye can be added to the adhesive film forming material of the present invention in order to further improve the resolution during patterning in multilayer lithography. The dye is not particularly limited as long as it is a compound that has a suitable absorption at the exposure wavelength, and various known compounds can be widely used. Examples include benzenes, naphthalenes, anthracenes, phenanthrenes, pyrenes, isocyanuric acids, and triazines.

[0089] Furthermore, the adhesion film forming material of the present invention is extremely useful as an adhesion film material for multi-layer resist processes such as a four-layer resist process using a resist underlayer film and a silicon-containing intermediate film.

[0090] The silicon-containing intermediate film can be a silicon-containing resist intermediate film or an inorganic hard mask intermediate film according to the pattern forming method described later. The inorganic hard mask intermediate film is preferably selected from a silicon oxide film, a silicon nitride film, and a silicon oxynitride film.

[0091] [Method of forming adhesive film] The present invention provides a method for forming an adhesion film that has high adhesion to an overlying resist film and has an effect of preventing collapse of a fine pattern in a fine patterning process using a multilayer resist method in a semiconductor device manufacturing process, using the above-mentioned adhesion film forming material.

[0092] In the method for forming an adhesive film of the present invention, the adhesive film forming material is coated on a substrate to be processed by spin coating or the like. After spin coating, the organic solvent is evaporated, and baking (heat treatment) is performed to promote a crosslinking reaction in order to prevent intermixing with the resist upper layer film or the silicon-containing intermediate film. The baking is preferably performed at 100°C or higher and 300°C or lower for 10 to 600 seconds, more preferably at 200°C or higher and 250°C or lower for 10 to 300 seconds. Considering the damage to the adhesive film and the influence on the deformation of the wafer, the upper limit of the heating temperature in the wafer process of lithography is preferably 300°C or lower, more preferably 250°C or lower.

[0093] In addition, in the method for forming an adhesion film of the present invention, the adhesion film forming material of the present invention is coated on a substrate to be processed by spin coating or the like as described above, and the adhesion film forming material is baked in an atmosphere with an oxygen concentration of 0.1% or more and 21% or less to harden the adhesion film, thereby forming the adhesion film. By baking the adhesion film forming material of the present invention in such an oxygen atmosphere, a sufficiently hardened film can be obtained.

[0094] The atmosphere during baking may be air or may contain an inert gas such as N2, Ar, or He. In this case, the atmosphere may have an oxygen concentration of less than 0.1%. The baking temperature and the like may be the same as above. Even if the substrate to be processed contains a material that is unstable when heated in an oxygen atmosphere, the crosslinking reaction during the formation of the adhesive film can be promoted without causing deterioration of the substrate to be processed.

[0095] [Pattern formation method] In the present invention, the following two methods are provided as a pattern formation method by a four-layer resist process using the above-mentioned adhesive film-forming material. First, a method for forming a pattern on a substrate to be processed is provided, which comprises at least forming a resist underlayer film on the substrate to be processed using an organic film material, forming a silicon-containing intermediate film (silicon-containing resist intermediate film) on the resist underlayer film using a resist intermediate film material containing silicon atoms, forming an adhesion film on the silicon-containing resist intermediate film using the adhesion film-forming material of the present invention, forming a resist upperlayer film on the adhesion film using a resist upperlayer film material consisting of a photoresist composition to form a multi-layer resist film, exposing a pattern circuit region of the resist upperlayer film, and then developing with a developer to form a resist upperlayer film pattern on the resist upperlayer film, etching the adhesion film using the obtained resist upperlayer film pattern as an etching mask to form an adhesion film pattern, etching the silicon-containing resist intermediate film using the obtained adhesion film pattern as an etching mask to form a silicon-containing resist intermediate film pattern, etching the resist underlayer film using the obtained silicon-containing resist intermediate film pattern as an etching mask to form a resist underlayer film pattern, and further etching the substrate to be processed using the obtained resist underlayer film pattern as an etching mask to form a pattern on the substrate to be processed.

[0096] As the silicon-containing resist intermediate film in the four-layer resist process, a polysilsesquioxane-based intermediate film is also preferably used. By imparting an anti-reflection effect to the silicon-containing resist intermediate film, reflection can be suppressed. In particular, for 193 nm exposure, if a material containing many aromatic groups and having high substrate etching resistance is used as the resist underlayer film, the k value becomes high and the substrate reflection becomes high, but by suppressing reflection with the silicon-containing resist intermediate film, the substrate reflection can be reduced to 0.5% or less. As the silicon-containing resist intermediate film having an anti-reflection effect, anthracene is preferably used for 248 nm and 157 nm exposure, and polysilsesquioxane is preferably used for 193 nm exposure, which is pendant with a light-absorbing group having a phenyl group or a silicon-silicon bond and crosslinked with acid or heat.

[0097] In this case, the formation of the silicon-containing resist intermediate film by spin coating is easier and more cost-effective than the CVD method.

[0098] In addition, an inorganic hard mask intermediate film may be formed as the silicon-containing intermediate film. In this case, at least a resist underlayer film is formed on a substrate to be processed using an organic film material, an inorganic hard mask intermediate film selected from a silicon oxide film, a silicon nitride film, and a silicon oxynitride film is formed on the resist underlayer film, an adhesion film is formed on the inorganic hard mask intermediate film using the adhesion film forming material of the present invention, a resist upper layer film is formed on the adhesion film using a resist upper layer film material consisting of a photoresist composition, and a pattern circuit region of the resist upper layer film is exposed, and then developed with a developer to form a resist upper layer film pattern on the resist upper layer film, the adhesion film is etched using the obtained resist upper layer film pattern as an etching mask to form an adhesion film pattern, the inorganic hard mask intermediate film is etched using the obtained adhesion film pattern as an etching mask to form an inorganic hard mask intermediate film pattern, the resist underlayer film is etched using the obtained inorganic hard mask intermediate film pattern as an etching mask to form a resist underlayer film pattern, and further, the substrate to be processed is etched using the obtained resist underlayer film pattern as an etching mask to form a pattern on the substrate to be processed.

[0099] As described above, when forming an inorganic hard mask intermediate film on a resist underlayer film, a silicon oxide film, a silicon nitride film, and a silicon oxide nitride film (SiON film) can be formed by a CVD method, an ALD method, or the like. For example, a method for forming a silicon nitride film is described in JP-A-2002-334869 and WO-A-2004 / 066377. The thickness of the inorganic hard mask intermediate film is preferably 5 to 200 nm, more preferably 10 to 100 nm. In addition, as the inorganic hard mask intermediate film, a SiON film, which has a high effect as an anti-reflection film, is most preferably used. Since the substrate temperature during the formation of the SiON film is 300 to 500°C, the resist underlayer film needs to withstand a temperature of 300 to 500°C.

[0100] The resist upper layer film in the four-layer resist process may be either positive or negative, and may be the same as a commonly used photoresist composition. After spin-coating the photoresist composition, pre-baking is performed, preferably at 60 to 180°C for 10 to 300 seconds. Thereafter, exposure is performed according to a conventional method, followed by post-exposure baking (PEB) and development to obtain a resist upper layer film pattern. The thickness of the resist upper layer film is not particularly limited, but is preferably 30 to 500 nm, and more preferably 50 to 400 nm.

[0101] A circuit pattern (resist upper layer film pattern) is formed on the resist upper layer film. In forming the circuit pattern, it is preferable to form the circuit pattern by lithography using light having a wavelength of 10 nm or more and 300 nm or less, direct drawing with an electron beam, nanoimprinting, or a combination of these.

[0102] Examples of the exposure light include high-energy rays with a wavelength of 300 nm or less, specifically far ultraviolet rays, KrF excimer laser light (248 nm), ArF excimer laser light (193 nm), F2 laser light (157 nm), Kr2 laser light (146 nm), Ar2 laser light (126 nm), soft X-rays (EUV) of 3 to 20 nm, electron beams (EB), ion beams, X-rays, and the like.

[0103] In forming the circuit pattern, it is preferable to develop the circuit pattern using an alkali developer or an organic solvent.

[0104] Next, etching is performed using the resist top layer film pattern as a mask. In the four-layer resist process, the adhesion film is etched using an oxygen-based gas with the resist top layer film pattern as a mask. This forms an adhesion film pattern.

[0105] Next, etching is performed using the obtained adhesive film pattern as a mask. The etching of the silicon-containing resist intermediate film or the inorganic hard mask intermediate film is performed using the adhesive film pattern as a mask with a fluorocarbon-based gas. In this way, a silicon-containing resist intermediate film pattern or an inorganic hard mask intermediate film pattern is formed.

[0106] The etching of the adhesion film may be carried out prior to and consecutively with the etching of the silicon-containing intermediate film, or the etching of the silicon-containing intermediate film may be carried out after etching only the adhesion film, for example by changing the etching apparatus.

[0107] Next, the resist underlayer film is etched using the obtained silicon-containing resist intermediate film pattern or inorganic hard mask intermediate film pattern as a mask.

[0108] The next step, etching of the substrate to be processed, can also be done by standard methods; for example, if the substrate to be processed is a SiO2, SiN, or silica-based low dielectric constant insulating film, etching is done mainly with fluorocarbon gases, and for p-Si, Al, or W, etching is done mainly with chlorine- or bromine-based gases. When etching the substrate with fluorocarbon gases, the silicon-containing intermediate film pattern in the three-layer resist process is peeled off at the same time as the substrate is processed. When etching the substrate with chlorine- or bromine-based gases, the silicon-containing intermediate film pattern must be peeled off by separate dry etching with fluorocarbon gases after substrate processing.

[0109] The substrate to be processed is not particularly limited, and may be a semiconductor device substrate, or a semiconductor device substrate having a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, or a metal oxide nitride film formed thereon. As the metal, silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or an alloy thereof may be used.

[0110] Specifically, substrates such as Si, α-Si, p-Si, SiO2, SiN, SiON, W, TiN, Al, etc., and substrates on which a layer to be processed is formed, etc. are used. As the layer to be processed, various low-k films such as Si, SiO2, SiON, SiN, p-Si, α-Si, W, W-Si, Al, Cu, Al-Si, etc. and their stopper films are used, and can be formed to a thickness of usually 50 to 10,000 nm, particularly 100 to 5,000 nm. When forming a layer to be processed, the substrate and the layer to be processed are made of different materials.

[0111] An example of a four-layer resist process is specifically shown below with reference to Fig. 1. In the four-layer resist process, as shown in Fig. 1(A), a resist underlayer film 3 is formed using an organic film material on a processable layer 2 laminated on a substrate 1, and then a silicon-containing intermediate film 4 is formed thereon, an adhesion film 5 is formed thereon using the adhesion film-forming material of the present invention, and a resist upper layer film 6 is formed thereon.

[0112] Next, as shown in FIG. 1(B), a desired portion 7 of the resist upper layer film is exposed, and PEB and development are performed to form a resist pattern 6a (FIG. 1(C)). Using the obtained resist pattern 6a as a mask, the adhesion film 5 is etched using an O2-based gas to form an adhesion film pattern 5a. (FIG. 1(D)). Using the obtained adhesion film 5a as a mask, the silicon-containing intermediate film 4 is etched using a CF2-based gas to form a silicon-containing intermediate film pattern 4a (FIG. 1(E)). After removing the adhesion film pattern 5a, using the obtained silicon-containing intermediate film pattern 4a as a mask, the resist underlayer film 3 is etched using an O2-based gas to form a resist underlayer film pattern 3a (FIG. 1(F)). Furthermore, after removing the silicon-containing intermediate film pattern 4a, the processed layer 2 is etched using the resist underlayer film pattern 3a as a mask to form a pattern 2a (FIG. 1(G)).

[0113] As described above, the pattern forming method of the present invention makes it possible to form a fine pattern on a substrate to be processed with high precision in a multi-layer resist process. EXAMPLES

[0114] The present invention will be described in more detail below with reference to Synthesis Examples, Comparative Synthesis Examples, Examples, and Comparative Examples, but the present invention is not limited thereto. The molecular weight was measured by the following method. The weight average molecular weight (Mw) and number average molecular weight (Mn) in terms of polystyrene were determined by gel permeation chromatography (GPC) using tetrahydrofuran as an eluent, and the polydispersity (Mw / Mn) was determined.

[0115] The polymers (A1) to (A6) and the comparative polymers (R1) to (R3) used as the resin (A) for the adhesive film-forming material were synthesized using the monomers (B1) to (B9) shown below. [ka]

[0116] [Synthesis Example 1] Synthesis of polymer (A1) In a 2L flask, 16.2g of 4-acetoxystyrene (B1) and 50g of tetrahydrofuran as a solvent were added. The reaction vessel was cooled to -70°C under a nitrogen atmosphere, and degassing under reduced pressure and nitrogen blowing were repeated three times. After warming to room temperature, 1.2g of AIBN (azobisisobutyronitrile) was added as a polymerization initiator, and the temperature was raised to 60°C, and the reaction was allowed to proceed for 15 hours. The reaction solution was added to a 1L solution of isopropyl alcohol, precipitated, and the resulting white solid was dissolved again in a mixed solvent of 100mL of methanol and 200mL of tetrahydrofuran, and 10g of triethylamine and 10g of water were added, and the acetyl group was deprotected at 70°C for 5 hours, and neutralized with acetic acid. The reaction solution was concentrated, dissolved in 100mL of acetone, precipitated in the same manner as above, filtered, and dried at 60°C to obtain a white polymer (A1). The polymer was analyzed by GPC. amount The average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined to be Mw=8,500 and Mw / Mn=1.68. [ka]

[0117] [Synthesis Example 2] Synthesis of polymer (A2) Into a 2L flask, 17.8g of 4-hydroxyphenyl methacrylate (B2) and 50g of tetrahydrofuran as a solvent were added. The reaction vessel was cooled to -70°C under a nitrogen atmosphere, and degassed under reduced pressure and nitrogen blowing were repeated three times. After heating to room temperature, 1.2g of AIBN (azobisisobutyronitrile) was added as a polymerization initiator, and the temperature was raised to 60°C, and the reaction was carried out for 15 hours. This reaction solution was added to 1L of an isopropyl alcohol solution to cause precipitation, and the resulting white solid was filtered and dried under reduced pressure at 60°C to obtain a white polymer (A2). The polymerization was confirmed by GPC. amount The average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined to be Mw=11,000 and Mw / Mn=2.11. [ka]

[0118] [Synthesis Examples 3 to 6] Synthesis of Polymers (A3) to (A6) Polymers (A3) to (A6) shown in Table 1 were obtained as products under the same reaction conditions as in Synthesis Example 2, except that the monomers shown in Table 1 were used. The weight average molecular weight (Mw) and dispersity (Mw / Mn) determined by GPC are also shown. [Table 1]

[0119] [Comparative Synthesis Example 1] Synthesis of Comparative Polymer (R1) Into a 2L flask, 19.2g of 4-methoxyphenyl methacrylate (B7) and 50g of tetrahydrofuran as a solvent were added. The reaction vessel was cooled to -70°C under a nitrogen atmosphere, and degassed under reduced pressure and nitrogen blowing were repeated three times. After heating to room temperature, 1.2g of AIBN (azobisisobutyronitrile) was added as a polymerization initiator, and the temperature was raised to 60°C, and the reaction was carried out for 15 hours. This reaction solution was added to 1L of an isopropyl alcohol solution to cause precipitation, and the resulting white solid was filtered and dried under reduced pressure at 60°C to obtain a white polymer (R1). The polymerization was confirmed by GPC. amountThe average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined to be Mw=11,700 and Mw / Mn=2.14. [ka]

[0120] [Comparative Synthesis Example 2] Synthesis of Comparative Polymer (R2) In a 2L flask, 23.4g of 3-tert-butyl-4-hydroxyphenyl methacrylate (B8) and 50g of tetrahydrofuran as a solvent were added. The reaction vessel was cooled to -70°C under a nitrogen atmosphere, and degassed under reduced pressure and nitrogen blowing were repeated three times. After heating to room temperature, 1.2g of AIBN (azobisisobutyronitrile) was added as a polymerization initiator, and the temperature was raised to 60°C, and the reaction was carried out for 15 hours. This reaction solution was added to 1L of isopropyl alcohol solution to precipitate, and the obtained white solid was filtered and dried under reduced pressure at 60°C to obtain a white polymer (R2). The polymerization was confirmed by GPC. amount The average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined to be Mw=8,700 and Mw / Mn=1.69. [ka]

[0121] [Comparative Synthesis Example 3] Synthesis of Comparative Polymer (R3) Into a 2L flask, 17.0g of 2-oxotetrahydrofuran-3-yl methacrylate (B9) and 50g of tetrahydrofuran as a solvent were added. The reaction vessel was cooled to -70°C under a nitrogen atmosphere, and degassed under reduced pressure and nitrogen blowing were repeated three times. After warming to room temperature, 1.2g of AIBN (azobisisobutyronitrile) was added as a polymerization initiator, and the temperature was raised to 60°C, and the reaction was carried out for 15 hours. This reaction solution was added to a 1L solution of isopropyl alcohol to cause precipitation, and the obtained white solid was filtered and dried under reduced pressure at 60°C to obtain a white polymer (R3). The polymerization was confirmed by GPC. amount The average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined to be Mw=9,700 and Mw / Mn=2.03. [ka]

[0122] Preparation of adhesive film forming materials (AL-1 to 17, comparative AL-1 to 9) The adhesive film-forming materials and comparative materials were prepared using the polymers (A1) to (A6) and comparative polymers (R1) to (R3), the crosslinking agents (X1) to (X4), the photoacid generators (P1) to (P3), and the thermal acid generator (AG1). The adhesive film-forming materials (AL-1 to 17, comparative AL-1 to 9) were prepared by dissolving the materials in the ratios shown in Table 2 using propylene glycol monomethyl ether acetate (PGMEA) containing 0.1 mass % of PF636 (manufactured by OMNOVA) and filtering through a 0.1 μm fluororesin filter. [ka]

[0123] [Table 2]

[0124] Example 1 Solvent Resistance Evaluation (Examples 1-1 to 1-17, Comparative Examples 1-1 to 1-9) The adhesive film forming materials (AL-1 to 17, Comparative AL1 to 9) prepared above were applied onto a silicon substrate, baked at 220°C for 60 seconds, the film thickness was measured, PGMEA solvent was dispensed onto it, left for 30 seconds, spin-dried, baked at 100°C for 60 seconds to evaporate the PGMEA solvent, the film thickness was measured again, and the difference in film thickness before and after PGMEA treatment was calculated to evaluate the solvent resistance. The results are shown in Table 3.

[0125] [Table 3]

[0126] As shown in Table 3, in Examples 1-1 to 1-17 using the adhesive film-forming material (AL-1 to 17) of the present invention, it is found that the film thickness is hardly reduced by the solvent treatment and a film with good solvent resistance is obtained. On the other hand, it is found that in Comparative Example 1-5 which does not contain a crosslinking agent, sufficient solvent resistance is not ensured. In addition, when Comparative Example 1-6 and Comparative Example 1-7 are compared, it is found that Comparative Example 1-6 which does not contain a thermal acid generator has insufficient curing properties, and when using crosslinking agent X3, it is necessary to combine it with a thermal acid generator. Furthermore, it is found that Comparative Examples 1-8 and 1-9 using crosslinking agent X4 do not ensure sufficient solvent resistance when baked at 220°C.

[0127] Example 2 Adhesion Test (Examples 2-1 to 2-17, Comparative Examples 2-1 to 2-5) The above adhesive film forming materials (AL-1 to 17, Comparative AL1 to 4, 7) were applied onto a SiO2 wafer substrate and baked for 60 seconds at 220°C in air using a hot plate to form an adhesive film with a thickness of 200 nm. The wafer with the adhesive film was cut into a 1 x 1 cm square, and aluminum pins with epoxy adhesive were attached to the cut wafers using a special tool. The aluminum pins were then attached to the substrate by heating at 150°C for 1 hour in an oven. After cooling to room temperature, the initial adhesion was evaluated by resistance using a thin film adhesion strength measuring device (Sebastian Five-A).

[0128] Figure 2 shows an explanatory diagram of the adhesion measurement method. In Figure 2, 8 is the silicon wafer (substrate), 9 is the cured film, 10 is the aluminum pin with adhesive, 11 is the support base, 12 is the grip, and 13 indicates the tensile direction. The adhesion strength is the average value of 12 measurements, and the higher the value, the stronger the adhesion of the adhesive film to the substrate. The adhesion was evaluated by comparing the obtained values. The results are shown in Table 4.

[0129] [Table 4]

[0130] As shown in Table 4, Examples 2-1 to 2-17, which used the adhesive film-forming material of the present invention (AL-1 to 17), were confirmed to have superior adhesion compared to Comparative Example 2-1, which contains a polymer that does not contain a hydroxyl group, and Comparative Example 2-2, which contains a polymer having a bulky substituent with 4 carbon atoms adjacent to the hydroxyl group. It can be seen that Examples 2-4 and 2-14 to 17, which contain a polymer having two hydroxyl groups at adjacent positions, have particularly excellent adhesion.

[0131] Example 3 Pattern formation test (Examples 3-1 to 3-17, Comparative Examples 3-1 to 3-5) On a silicon wafer substrate, spin-on carbon ODL-301 (carbon content 88% by mass) manufactured by Shin-Etsu Chemical Co., Ltd. was applied and baked at 350°C for 60 seconds to form a resist underlayer film with a thickness of 200 nm. A CVD-SiON hard mask intermediate film was formed thereon, and the above-mentioned adhesion film forming material (AL1-17, comparative AL1-4, 7) was further applied and baked at 220°C for 60 seconds to form an adhesion film with a thickness of 20 nm, on which a single layer resist for ArF of the resist upper layer film material was applied and baked at 105°C for 60 seconds to form a resist upper layer film with a thickness of 100 nm. An immersion protective film material (TC-1) was applied on the resist upper layer film and baked at 90°C for 60 seconds to form a protective film with a thickness of 50 nm.

[0132] The resist top layer material (ArF single layer resist) was prepared by dissolving a polymer (PRP-A1), an acid generator (PAG1), and a basic compound (Amine1) in a solvent containing 0.1 mass% FC-430 (Sumitomo 3M Limited) in the proportions shown in Table 5, and filtering the solution through a 0.1 μm fluororesin filter.

[0133] [Table 5]

[0134] Resist polymer: PRP-A1 Molecular weight (Mw)=8,600 Dispersity (Mw / Mn)=1.88 [ka]

[0135] Acid generator: PAG1 [ka]

[0136] Basic compound: Amine1 [ka]

[0137] The immersion protective film material (TC-1) was prepared by dissolving the protective film polymer (PP1) in an organic solvent in the ratio shown in Table 6, and filtering the solution through a 0.1 μm fluorine resin filter.

[0138] [Table 6]

[0139] Protective film polymer: PP1 Molecular weight (Mw)=8,800 Dispersity (Mw / Mn)=1.69 [ka]

[0140] Next, the pattern was exposed using an ArF immersion exposure apparatus (Nikon Corporation; NSR-S610C, NA 1.30, σ 0.98 / 0.65, 35 degree dipole s-polarized illumination, 6% halftone phase shift mask), baked at 100°C for 60 seconds (PEB), and developed with a 2.38 mass% tetramethylammonium hydroxide (TMAH) aqueous solution for 30 seconds to obtain a 40 nm 1:1 line and space pattern. of The cross-sectional shape and roughness were observed using an electron microscope. In addition, when the line dimension was narrowed by increasing the exposure dose, the minimum dimension at which the line could be resolved without collapsing was determined, and this was taken as the collapse limit (nm). The smaller the value, the higher the collapse resistance, making it preferable.

[0141] The cross-sectional shape of the obtained pattern was evaluated using an electron microscope (S-4700) manufactured by Hitachi, Ltd., and the pattern roughness was evaluated using an electron microscope (CG4000) manufactured by Hitachi High-Technologies Corp. The results are shown in Table 7.

[0142] [Table 7]

[0143] As shown in Table 7, Examples 3-1 to 3-17 using the adhesion film-forming material of the present invention (AL-1 to 17) exhibited superior collapse suppression performance compared to the comparative examples, and it was found that finer pattern formation was possible. Furthermore, it was found that by appropriately adjusting the photoacid generator, excellent pattern shape and pattern roughness were obtained. Comparative Examples 3-1 to 3-3, which did not contain the resin contained in the adhesion film-forming material of the present invention and had low adhesion, exhibited low pattern collapse suppression performance, and Comparative Example 3-4, which did not contain the photoacid generator, and Comparative Example 3-5, which did not contain the crosslinking agent contained in the adhesion film-forming material of the present invention, showed deterioration in the cross-sectional shape of the pattern.

[0144] From the above, the adhesion film forming material of the present invention has high adhesion to the resist overlying film and has the effect of preventing the collapse of a fine pattern, and is therefore extremely useful as an adhesion film material for use in a multilayer resist method. Furthermore, the pattern forming method of the present invention using this material makes it possible to form a fine pattern on a substrate to be processed with high precision.

[0145] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention. [Explanation of symbols]

[0146] 1...substrate, 2...processed layer, 2a...pattern (pattern formed on the processed layer), 3...resist underlayer film, 3a...resist underlayer film pattern, 4...silicon-containing intermediate film, 4a...silicon-containing intermediate film pattern, 5...adhesive film, 5a...adhesive film pattern, 6: resist upper layer film; 6a: resist upper layer film pattern; 7: exposed portion; 8...silicon wafer; 9...hardened film; 10...aluminum pin with adhesive; 11...support base; 12...grip; 13...pulling direction.

Claims

1. An adhesion film forming material for an adhesion film formed between a SiO2 film and a chemically amplified positive ArF resist, the adhesion film forming material comprising (A) a resin having a structural unit represented by the following general formula (1), (B) a crosslinking agent containing one or more compounds represented by the following general formula (2), (C) a photoacid generator, and (D) an organic solvent. 【Chemistry 1】 (In the formula, R 01 is a hydrogen atom or a methyl group, R 02 is an alkyl group having 1 to 3 carbon atoms, m is an integer of 1 or 2, n is an integer of 0 to 4, and m+n is an integer of 1 or more and 5 or less. X is -C(=O)O-. 【Chemistry 2】 (In the formula, Q is a single bond or a q-valent hydrocarbon group having 1 to 20 carbon atoms. R 03 is a hydrogen atom or a methyl group; and q is an integer from 1 to 5.

2. 2. The adhesive film forming material according to claim 1, wherein the photoacid generator (C) is one or more compounds represented by the following general formula (3): 【Chemistry 3】 (In the formula, R 04 , R 05 and R 06 each independently represents a linear alkyl or alkenyl group having 1 to 10 carbon atoms, which may be substituted with a heteroatom or may have a heteroatom interposed therebetween, or a branched or cyclic alkyl or alkenyl group having 3 to 10 carbon atoms, which may be substituted with a heteroatom or may have a heteroatom interposed therebetween, or an aryl or aralkyl group having 6 to 18 carbon atoms, which may be substituted with a heteroatom or may have a heteroatom interposed therebetween. 04 , R 05 and R 06 Any two of may be bonded to each other to form a ring together with the sulfur atom in the formula. - represents either the following general formula (4) or (5). 【Chemistry 4】 (In the formula, R 07 and R 08 each independently represents a monovalent hydrocarbon group containing an aliphatic ring structure having 3 to 40 carbon atoms, which may be substituted with a heteroatom and may be interrupted by a heteroatom.

3. 3. The adhesive film forming material according to claim 2, wherein the general formula (4) is represented by the following general formula (4'): 【Chemistry 5】 (In the formula, R 09 R represents a hydrogen atom or a trifluoromethyl group. 10 represents a monovalent hydrocarbon group containing an aliphatic ring structure having 3 to 30 carbon atoms, which may be substituted with a heteroatom or may be interrupted by a heteroatom.

4. 4. The adhesive film forming material according to claim 1, wherein the weight average molecular weight of the resin (A) is 1,000 to 20,000.

5. 5. The adhesion film forming material according to claim 1, wherein the content of the (B) crosslinking agent is 10% by mass to 50% by mass with respect to the content of the (A) resin.

6. The adhesion film forming material according to any one of claims 1 to 5, characterized in that the content of the photoacid generator (C) is 1% by mass to 20% by mass with respect to the content of the resin (A).

7. 7. The adhesive film forming material according to claim 1, further comprising at least one of a surfactant, a plasticizer and a dye.

8. 8. The adhesive film forming material according to claim 1, which does not contain a thermal acid generator.

9. A method for forming a pattern on a workpiece substrate, comprising the steps of: (II-1) forming a resist underlayer film on a substrate to be processed; (II-2) A step of forming a SiO2 film on the resist underlayer film; (II-3) A step of forming an adhesion film by applying the adhesion film forming material according to any one of claims 1 to 8 onto the SiO2 film and then heat-treating the material; (II-4) forming a chemically amplified positive ArF resist on the adhesion film using a photoresist material; (II-5) a step of pattern-exposing the chemically amplified positive ArF resist and then developing it with a developer to form a pattern in the chemically amplified positive ArF resist; (II-6) A step of transferring the pattern to the adhesive film by dry etching using the chemically amplified positive ArF resist on which the pattern has been formed as a mask; (II-7) A process of transferring the pattern to the SiO 2 film by dry etching using the adhesive film on which the pattern is formed as a mask; and (II-8) A step of transferring a pattern to the resist underlayer film by dry etching using the SiO2 film to which the pattern has been transferred as a mask; A pattern forming method comprising the steps of:

10. 10. The pattern forming method according to claim 9, wherein the SiO2 film is formed by a CVD method or an ALD method.

11. 11. The pattern forming method according to claim 9, wherein a method for forming a circuit pattern on the chemically amplified positive ArF resist is performed by photolithography having a wavelength of 10 nm or more and 300 nm or less, direct writing using an electron beam, nanoimprinting, or a combination thereof.

12. 12. The method for forming a pattern according to claim 9, wherein the development is carried out using an alkali development or an organic solvent.

13. 13. The pattern forming method according to claim 9, wherein the workpiece substrate is a semiconductor device substrate, or a semiconductor device substrate having any one of a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, and a metal oxide nitride film formed thereon.

14. 14. The pattern formation method according to claim 13, wherein the metal is silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or an alloy thereof.

15. A method for forming an adhesion film that functions as an adhesion layer used in a manufacturing process of a semiconductor device, comprising spin-coating an adhesion film-forming material according to any one of claims 1 to 8 onto a substrate to be processed, and heat-treating the substrate coated with the adhesion film-forming material at a temperature of 100°C or higher and 300°C or lower for 10 to 600 seconds to form a hardened film.

16. A method for forming an adhesion film that functions as an adhesion layer used in the manufacturing process of a semiconductor device, comprising spin-coating an adhesion film-forming material according to any one of claims 1 to 8 onto a substrate to be processed, and heat-treating the substrate coated with the adhesion film-forming material in an atmosphere having an oxygen concentration of 0.1% or more and 21% or less to form a hardened film.

17. A method for forming an adhesion film that functions as an adhesion layer used in the manufacturing process of a semiconductor device, comprising spin-coating an adhesion film-forming material according to any one of claims 1 to 8 onto a substrate to be processed, and heat-treating the substrate coated with the adhesion film-forming material in an atmosphere with an oxygen concentration of less than 0.1%, thereby forming a hardened film.

Citation Information

Patent Citations

  • Tape end detecting circuit of magnetic recorder and reproducer

    JP1982008938A

  • Composition for forming antireflective film for use in lithography

    WO2003017002A1

  • Resist underlayer film forming composition including polymer having structure unit having urea bond

    WO2018143359A1